The Gospel of John - Michaels, J. Ramsey (Grand Rapids, Mich. : William B. Eerdmans Pub., 2010)
In this detailed commentary J. Ramsey Michaels gives primary attention to the Gospel of John in its present form rather than to the sources or traditions behind it. Michaels examines both the Gospel's literary character and its theological significance for the Christian community in its own time and through the ages.
The nature of John's gospel -- The authorship of the gospel -- Truth claims -- John and the other gospels -- The structure of John's gospel -- Location and date -- Preamble : the light -- The testimony of John -- Jesus' self-revelation to the world -- Jesus' self-revelation to the disciples -- Verification of Jesus' self-revelation in his passion and resurrection.
Includes bibliographical references (p. xvi-xxvii) and indexes.
Keywords: Bible. -- Commentaries